Transcendent individual : towards a literary and liberal anthropology - Rapport, Nigel, 1956- (Routledge, 1997)
"How might anthropology seem if it were written in celebration of individuality - of the individual's conscious and creative engagement with socio-cultural milieux - and if it were committed to a liberal agenda which sought to cherish and defend that individuality?" "Transcendent Individual argues for just such a commitment: a reappraisal of the place of the individual in anthropological theorising and ethnographic writing, and a social-scientific appreciation of the individual as methodological, moral, pragmatic and aesthetic subject. Here is an anthropological account of individual creativity, of the narrativity of individual expression, of the originality of individual becoming, and of the morality of the individual body." "Drawing widely on ethnographic and theoretic materials, and bringing into debate a range of voices - Nietzsche, Wilde and Forster, Bateson and Gerald Edelman, George Steiner, Richard Rorty and John Berger, Edmund Leach and Anthony Cohen - the book approaches individuality in terms of a range of issues: biological integrity, consciousness, agency, democracy, discourse, knowledge, consumerism, globalism and play."--Jacket